Northern Red-Oak Kermes, Kermes Scale (suggested common names), Allokermes kingii (Cockerell) (Insecta: Hemiptera: Coccoidea: Kermesidae) - Jay Cee Turner; Eileen Buss (EDIS)
In North America there are 32 species of Kermesidae in five genera, but in northeastern North America there are only nine species in four genera (Eriokermes, Nanokermes, Allokermes, and Kermes). The Allokermes spp. that are of economic importance in Florida are A. cueroensis (Cockerell), A. galliformis (Riley), and A. kingii (Cockerell). The kermes scale, Allokermes kingii (Cockerell), is an important pest on oak (Quercus spp.) trees. This document is EENY-338, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2004.